Examining the relationship between market orientation and export performance: the moderating role of competitive Intensity - Lengler, J.; Sousa, C. M. P.; Marques, C. (Advances in International Marketing, 2014)
Despite some attempts to integrate the market orientation construct into the international marketing area, most conceptual and empirical studies have been conducted in the context of domestic operations. To address this gap we examine whether competitive intensity moderates the relationships among the components of market orientation and export performance. Data was used from 197 Brazilian export companies. Results suggest that interfunctional coordination enhances customer and competitor orientation. Moreover, customer orientation has no direct effect on export performance, while competitor orientation has a positive effect on firm’s international performance. Findings also indicate that competitive intensity moderates all the relationships tested in the model.